Simultaneous enhancement of critical heat flux and heat transfer coefficient via in-situ deposition of ionic liquids during pool boiling. (July 2023) - Upadhyay, Avinash; Kumar, Brijesh; Kumar, Nirbhay; Raj, Rishi
Highlights: Boiling with aqueous solution of various imidazolium ionic liquids (ImIL) performed. First demonstration of critical heat flux (CHF) enhancement with soluble additives. Short-chain ImILs such as [C2 mim][Cl] exhibits ≈ 1.6 × CHF in comparison to water. Gradual deposition of ImIL on heater during boiling responsible for CHF enhancement. Increase in chain length boosts heat transfer coefficient (HTC) at the cost of CHF. Chain-length tuned to 4 – 6 C atoms to show simultaneous CHF and HTC enhancement. Abstract: Two-phase heat transfer processes such as boiling are required to address waste heat management challenges. Among the various regimes, the nucleate boiling regime, which relies on the ebullition cycle to dissipate large amounts of heat within narrow temperature budgets is desired in such applications. However, an insulating vapor blankets the heater at higher heat fluxes to interrupt this high heat transfer coefficient (HTC) regime. This limiting heat flux beyond which a thermal runaway occurs in boiling systems is known as the critical heat flux (CHF). Accordingly, easy-to-implement and reliable strategies for simultaneous enhancement in HTC and CHF are desired. Typical surface modification/coating strategies used in this regard are often expensive and suffer from the issues of delamination and fouling. Here we utilize aqueous solutions of imidazolium ionic liquids (ImILs) to propose a facile, scalable, and robust strategy to address these issues. We show that the in-situ deposition of short-chain ImILs such as [C2 mim][Cl] enhances heater surface wettability to remarkably increase the CHF to ≈ 1600 kW / m 2, i.e., ≈ 1.6 × increase compared to the baseline case of pure water. We explain the mechanism of this atypical CHF enhancement with molecular additives via thorough surface tension, foamability, surface, and wettability characterization experiments. We next vary the hydrophobic chain length of the ImILs to facilitate a simultaneous enhancement in CHF and HTC. We perform a quantitative comparison with the existing studies in the literature to demonstrate the potential of our approach. Ease of implementation along with the flexibility to favorably manipulate the heater surface and the boiling fluid properties simultaneously by tuning the structure of ImILs are promising for current and future thermal management challenges. Graphical abstract: Image, graphical abstract